Komparasi Penerapan Metode Syawir dalam Mengembangkan Pemahaman Santri (Studi di Pesantren At Thohiriyyah, Al Hidayah dan Darul Abror) - Zaennuri, Ahmad; Harisatunisa (Jurnal Pendidikan Agama Islam, 2025)
In the learning activities of madrasah diniyyah in Islamic boarding schools, teachers must determine the appropriate method to use in order to support the achievement of learning objectives. One of the madrasah diniyyah teaching methods applied at At Thohiriyah, Al Hidayah, and Darul Abror Islamic boarding schools is the syawir method. The syawir method is a student-centered approach that focuses on developing students' abilities in discussion and critical thinking. The purpose of this research is to identify the comparative implementation of the syawir method in improving students' understanding at At Thohiriyah, Al Hidayah, and Darul Abror Islamic boarding schools. This study uses a qualitative method with data collection techniques in the form of interviews, observations, and documentation. Then in analyzing the data, the researcher uses data reduction methods, data presentation and drawing conclusions. The results of the study indicate that the procedure for implementing the syawir method in the At Thohiriyyah, Al Hidayah and Darul Abror Islamic boarding schools in general has several similarities in its stages but differs in its operations adjusted to the technical implementation of each boarding school, such as syawir preparation, group formation and selection of materials, place and time and especially in the implementation of the syawir method carried out in the At Thohiriyyah, Al Hidayah and Darul Abror Islamic boarding schools have similarities, but the procedures and methods of implementation are different adjusted to the characteristics of each boarding school. However, learning using the syawir method is carried out with the same goal of providing opportunities for students to solve their own problems by exchanging ideas with their peers so that they can train themselves to think critically and develop students' understanding